Economy Wide Impact of the Trade Integration between Japan and India: A Computable General Equilibrium Analysis - Biswa Nath Bhattacharyay; Kakali Mukhopadhyay (Center for Economic Studies and ifo Institute (CESifo), 2013)
Japan and India signed the much-awaited Comprehensive Economic Partnership Agreement (CEPA) on 16th February 2011. The CEPA will eliminate tariff on goods that account for 94% of their two way trade over ten years and will boost bilateral trade and investment. Indian exports which were subject to rigid standards will find it easier to enter Japanese markets. On the other hand, reduction of tariffs would help Japanese exports to exploit the growing Indian market. In this background, the study evaluates the economy wide impact of the proposed CEPA between India and Japan at 2020. The study has used a widely recognized global Computable General Equilibrium (CGE) model. Results show a marginal increase in output growth for India and Japan in 2020 after tariff reduction compared to Business as Usual (BAU) scenario. A marginal export growth is expected for both the countries compared to BAU 2020. A fair amount of trade creation within these two countries is expected to occur. India would likely to increase its export to Japan by I8.25%, while for Japan it will be only 4.65% by 2020. The proposed CEPA will also improve the welfare of both the countries at 2020. An important finding of the study is that in spite of tariff liberalization in agriculture sector which is protected through stringent tariff and non-tariff barriers, Japan will witness considerable welfare gain. On the whole, it reflects that compared to Japan, India is expected to gain more during the 2010-2020 from the successful implementation of CEPA. The triple disasters (earthquake, Tsunami and radiation leaks) in Japan in March 2011 will have short-term negative impacts on the economy but is unlikely to affect the expected gains from CEPA between India and Japan. The short negative impact may be significant but in the long-run Japanese economy will expand through reconstruction efforts and return to productive activities leading towards enhanced economic cooperation between the two countries.
Keywords: F10; F20; Q10; Q40; R40; 330; India; Japan; Asia; economic cooperation; trade and investment; Free Trade Agreement; Comprehensive Economic Partnership Agreement; CGE Model